Political (Electoral) Activity of Poles in Romanian Bukovina (In the Light of Field Research) - Rudowski, Andrzej; Zenderowski, Radosław (Political Preferences, 2019)
The article presents the results of field research conducted among Poles inhabiting Bukovina in autumn 2016. The main goal and subject of the research conducted by means of an In-Depth Interview (IDI) was the political activity (especially electoral activity) and political views of local Poles. The article analyzes closely such issues as: (a) the degree of interest in politics; (b) support for particular political parties; (c) motivation behind support for particular parties; (d) activities of Poles in local government elections; (e) ways of choosing local leaders; (f) comparison of political activities shown by Poles and Romanians; (g) the role of a Polish member of parliament in Bucharest; (h) political activities of Poles outside the Association of Poles. The article presents synthetic conclusions from the conducted research and quotes selected fragments of respondents’ statements.